Freezing Temperature and Freezing Menstruum on the Survival of Selected Marine Bacteria - Thampuran, Nirmala; K., Gopakumar (Fishery Technology, 2025)
The survival pattern of dominant bacterial genera encountered in fishery environs viz. Pseudomonas, Moraxella, Acinetobacter, Vibrio, Flavobacterium, Micrococcus and Bacillus were investigated at frozen storage temperature of -39±2°C and -20±2°C in various suspending fluids over a period of one year. The survival was maximum in fish muscle substrate for Vibrio, Moraxella, Acinetobacter, Micrococcus, and Bacillus species. For genera Pseudomonas and Flavobacterium, there was no significant difference in survival among the va rious freezing menstruum. Maximum reduction in cell numbers occurred during freezing period or in the period immediately after freezing. Based on the studies, the sensitivity of the bacterial genera to frozen storage was in the order of Vibrio> Bacillus, > Pseudomonas > Moraxella > Acinetobacter > Flavobacterium > Micrococcus.